Here's the question you clicked on:
careless850
William solved the system of equations below. What mistake did he make in his work? 3x + y = 6 x − 2y = 2 y = 6 + 3x x − 2(6 + 3x) = 2 x − 12 − 6x = 2 −5x − 12 = 2 + 12 +12 x = 2.8 3(2.8) + y = 6 8.4 + y = 6 −8.4 −8.4 y = −2.4 He should have substituted 6 − 3x. He combined like terms incorrectly. It should have been 5x instead of −5x. He made a mistake in distributing −2. He made no mistake.
\[3x+y=6\]Implies\[y=6-3x\]Not\[y=6+3x\]Choose your answer, accordingly.